2007
DOI: 10.1677/joe.1.07049
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal nuclear genome on the timing of puberty in mice offspring

Abstract: The timing of puberty is a complex trait which is regulated by environmental and genetic factors, but the detailed regulatory mechanism remains elusive. Maternal nutrition administration during late gestation in rats revealed that the time of onset of puberty in daughter rats was influenced by the mother's nutritional and physiological status during the embryonic development period. In this study, the potential effects of the maternal nuclear genome on the timing of puberty of offspring were investigated. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…Our previous data showed that the heritability of the timing of puberty in direct and reciprocal crosses between B6 and C3H inbred mice was 68.51% and 63.97%, respectively [16]. In this study, a QTL on chromosome X, which explained 0.5% of variation to this trait,was identified by whole genome scanning in two reciprocal pedigrees and was further confirmed and refined in mCSS and mISCS populations.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Our previous data showed that the heritability of the timing of puberty in direct and reciprocal crosses between B6 and C3H inbred mice was 68.51% and 63.97%, respectively [16]. In this study, a QTL on chromosome X, which explained 0.5% of variation to this trait,was identified by whole genome scanning in two reciprocal pedigrees and was further confirmed and refined in mCSS and mISCS populations.…”
Section: Discussionsupporting
confidence: 69%
“…The distributions of age at vaginal opening in three pedigrees including parental strains, F1 hybrids and F2 hybrids were reported to be normal in our previous study [16]. The data showed that the heritability of the age at vaginal opening in direct and reciprocal crosses between B6 and C3H inbred mice is 68.51% and 63.97% respectively.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Beginning on the day of weaning, the dates of VO for females and BPS for males were recorded. In female mice, VO was determined by daily inspection and recorded as the day on which the vaginal orifice transitioned from tightly closed to patent (Nelson et al, 1990; Azooz et al, 2001; Zhou et al, 2007; Brill and Moenter, 2009). The opening of the vaginal cavity to the skin is an event occurring around the fifth week of life that can be induced in sexually immature mice by beta-estradiol injections (Rodriguez et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Behavioral changes have also been observed in hybrids, such as the temperament differences commonly reported between hinnies (donkey mother and horse father) and mules (horse mother and donkey father) (Gray, 1972). In the laboratory, the reciprocal breeding of various inbred and outbred rodent strains and species has been extremely useful in screening for parent-of-origin effects on behavioral and physiological phenotypes such as emotional reactivity (Calatayud & Belzung, 2001;Carola, Frazzetto, & Gross, 2006;Roy, Merali, Poulter, & Anisman, 2007), maternal care (Calatayud, Coubard, & Belzung, 2004;Carola et al, 2008;Shoji & Kato, 2009), infanticide (Perrigo et al, 1993), aggression (Carlier, Roubertoux, & Pastoret, 1991;Platt & Maxson, 1989), sex (McGill & Manning, 1976), forced ethanol intake (Gabriel & Cunningham, 2008), calcium taste preference (Tordoff, Reed, & Shao, 2008), activity (Dohm, Richardson, & Garland, 1994;Massett & Berk, 2005;Price & Loomis, 1973), cerebellar development (Cooper, Benno, Hahn, & Hewitt, 1991), peripheral nerve conductivity (Hegmann & White, 1973), central estrogen receptor a distribution (Kramer, Carr, Schmidt, & Cushing, 2006), and puberty onset (Zhou et al, 2007).…”
Section: Introductionmentioning
confidence: 99%